ReOrienting the Sasanians : East Iran in Late Antiquity - Rezakhani, Khodadad (Edinburgh studies in ancient Persia., 2017)
A narrative history of Central Asia after the Greek dynasties and before Islam. Central Asia is commonly imagined as the marginal land on the periphery of Chinese and Middle Eastern civilisations. At best, it is understood as a series of disconnected areas that served as stop-overs along the Silk Road. However, in the mediaeval period, this region rose to prominence and importance as one of the centres of Persian-Islamic culture, from the Seljuks to the Mongols and Timur. Khodadad Rezakhani tells the back story of this rise to prominence, the story of the famed Kushans and mysterious ÃǾ²Ơ℗Asian Huns', and their role in shaping both the Sasanian Empire and the rest of the Middle East. Contextualises Persian history in relation to the history of Central Asia Extends the concept of late antiquity further east than is usually done Surveys the history of Iran and Central Asia between 200 and 800 bc and contextualises the rise of Islam in both regions "Central Asia is commonly imagined as the marginal land on the periphery of Chinese and Middle Eastern civilisations. At best, it is understood as a series of disconnected areas that served as stop-overs along the Silk Road. However, in the mediaeval period, this region rose to prominence and importance as one of the centres of Persian-Islamic culture, from the Seljuks to the Mongols and Timur. Khodadad Rezakhani tells the back story of this rise to prominence, the story of the famed Kushans and mysterious 'Asian Huns', and their role in shaping both the Sasanian Empire and the rest of the Middle East